True inclusion: evaluation protocol for an approach to increase meaningful participation of children with disability in athletics - Abby Haynes; Simone Pearce; Kate Kirby; Dominique Moritz; Kerry West; Kerry West; Suzy Green; Christine McCoombes; Catherine Sherrington (Frontiers Media S.A., 2024)
Children with disability face many barriers to participating in community sports. Little Athletics Australia aims to increase fair and meaningful inclusion via a new structure which will enable all children to take part in the same contest by competing for their 'personal best' score. Named the True Inclusion Method (TIM), this new structure will be piloted in 13 sites across six states. Formative evaluation of this pilot will critique TIM and its implementation using observations of events, and interviews and surveys with child athletes with and without disability, their parents/carers and Little Athletics volunteers. Implementation outcomes are acceptability, appropriateness, adoption, feasibility and fidelity. Qualitative data will be analysed thematically. TIM is designed to encourage inclusive participation by children with disability in sporting events, and to improve the competitive experience for all children by celebrating personal achievement and fostering fun.